PENERAPAN METODE WAHDAH DALAM KEGIATAN TAHFIDZ QUR’AN PADA SANTRI PONDOK PESANTREN TAHFIDZUL QUR’AN DARUL HIKAM JOMBANG - Dewi Hajar; Muhammad Hanief; Mutiara Sari Dewi (VICRATINA, 2022)
This research is motivated by a phenomenon the implementation of wahdah method in tahfidz Qur'an activities at Tahfidzul Qur'an Islamic Boarding School Darul Hikam Jombang. The purpose of this study is to describe how the planning, implementation process, and the results of the application wahdah method in tahfidz Qur'an activities at the Tahfidzul Qur'an Islamic Boarding School Darul Hikam Jombang students. This research uses a qualitative approach with a descriptive type. Data collection were carried out using observation, unstructured interviews, and documentation techniques. Sources of data taken from primary data and secondary data. The data analysis techniques in this study include data collection, data condensation, data presentation, and drawing conclusions. Based on the research that has been done, the researchers obtained the results that the planning for implementing the wahdah method at the Tahfidzul Qur'an Islamic boarding school Darul Hikam Jombang includes several stages, namely identifying the character of students, formulating goals, time management, and evaluating the wahdah method program for improvements. The implementation of the wahdah method has been said to be going well, it's just that there are obstacles related to time management. The results of the application of the wahdah method in tahfidzul Qur'an activities at the Tahfidzul Qur'an Islamic Boarding School Darul Hikam Jombang students are increasing the memory of the students in memorizing the Qur'an so that they are able to memorize the Qur'an faster than before with using rhythm and reading that is good and correct in accordance with the law of reading in the science of recitation